The nucleotide sequence of a major glutamine tRNA from rat liver - Yang, Julia A. (1983)
A major glutamine tRNA from rat liver was purified. Post-labeling techniques showed its nucleotide sequence to be: pG-G-U-U-C-C-A-U-m(1)G-G-U-G-ψ-A-A-D-Gm-G-D-D-A-G-C-A-C-U-C-U-G-G-A-Cm-U-C-U-G-A-A-ψ-C-C-A-G-C-G-A-U-m(5)C-m(5)C-G-A-G-ψ-ψ-C-A-m(1)A-A-U-C-U-C-G-G-U-G-G-A-A-C-C-U-C-C-A(OH).